MITIGASI DAERAH RAWAN TANAH LONGSOR MENGGUNAKAN TEKNIK PEMODELAN SISTEM INFORMASI GEOGRAFIS; STUDI KASUS: KECAMATAN SUMEDANG UTARA DAN SUMEDANG SELATAN - Mubekti Mubekti (Jurnal Teknologi Lingkungan, 2008)
Landslide is the main natural disaster in the study area of North Sumedang and South Sumedang sub-districts. The spatial distribution of landslide hazard and risk are not available yet that important for decision making. The aim of research is to providegeographic information system technology for developing a model for landslide hazard mitigation. The results show that a part of the area in the North Sumedang and South Sumedang subdistrict has moderate class covering 8.460,41 Ha (65,5%) and high landslide hazard is covering 2.798,44 Ha (21,67%), low landslide hazard zone = 1.570,25 Ha (12,16%) and very low landslide hazard 85,69 Ha (0,66%). By combining landslide hazard and property value, a prediction of landslide risk was produced. Despite the majority of the area has low risk class (9.564,16 Ha/74,07%), but the highrisk area occurred in minimal places (86,44 Ha/0,67%). This phenomena showed that area with high potential level of landslide hazard is not always having a high value of risk. Since the risk calculation is determined by properties value such as:infrastructure, road network and land use. While the landslide hazardous level is determined by natural factors such as : slope, soil type, geology and land use.